2020
DOI: 10.3390/antiox9020147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound-Treated Arabinoxylans on the Oxidative Stability of Soybean Oil

Abstract: Arabinoxylans (AX) are polysaccharides with antioxidant activity and emulsifying properties, which make them an attractive alternative for its potential application as a natural antioxidant in oils. Therefore, this work aimed to investigate the effect of ultrasonic treatment of AX on their antioxidant capacity and its ability to improve the oxidative stability of soybean oil. For this purpose, AX were exposed to ultrasonic treatment at 25% (100 W, AX-1) and 50% (200 W, AX-2) power and an operating frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The AC in MBAX determined by the ABTS method (25 μmol TE g −1 ) was slightly higher than those reported in other AX recovered from nixtamalized maize (6.09–21.27 μmol TE g −1 ), 22,52 but lower than those reported for AX from distiller's dried grains with solubles (32.09–68.05 μmol TE g −1 ) 52‐54 . By using the DPPH method, MBAX registered a lower AC (20 μmol TE g −1 ) than those found in other AX extracted from nixtamalized maize (2909–31.69 μmol TE g −1 ) 21 and distiller's dried grains with solubles (28.00–44.30 μmol TE g −1 ) 52‐55 …”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The AC in MBAX determined by the ABTS method (25 μmol TE g −1 ) was slightly higher than those reported in other AX recovered from nixtamalized maize (6.09–21.27 μmol TE g −1 ), 22,52 but lower than those reported for AX from distiller's dried grains with solubles (32.09–68.05 μmol TE g −1 ) 52‐54 . By using the DPPH method, MBAX registered a lower AC (20 μmol TE g −1 ) than those found in other AX extracted from nixtamalized maize (2909–31.69 μmol TE g −1 ) 21 and distiller's dried grains with solubles (28.00–44.30 μmol TE g −1 ) 52‐55 …”
Section: Resultscontrasting
confidence: 56%
“…[52][53][54] By using the DPPH method, MBAX registered a lower AC (20 μmol TE g −1 ) than those found in other AX extracted from nixtamalized maize (2909-31.69 μmol TE g −1 ) 21 and distiller's dried grains with solubles (28.00-44.30 μmol TE g −1 ). [52][53][54][55] Fine structural features and antioxidant capacity relationship It has been reported that FA content in AX is positively correlated with the polysaccharide AC. [56][57][58] Similarly, it has been observed that the release of FA from AX by enzymatic or chemical treatment substantially decreases its AC.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…For the specific modification of food-derived proteins, the ultrasound processing is considered a standard and effective modification technology [ 8 ]. UST is also successfully exploited as an extraction assisting process [ 9 , 10 , 11 ]. The fast mass transfer has been observed during the ultrasound-assisted extraction of polyphenols and other antioxidant compounds from different matrix [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heat-induced haemolysis. The assay was established as described by Mendez-Encinas et al (2023). Briefly, blood cell suspension (50 μL) and 50 μL of durian fruit rind extract and fractions at different concentrations (50-200 μg mL À1 ) were mixed with 1.95 mL of phosphate-buffered saline (PBS).…”
Section: Membrane Lysis Assaymentioning
confidence: 99%